Humour's critical capacity in the context of South African dance, with two related analyses - Elliott, Nicola (Rhodes University, Faculty of Humanities, Department of Drama, 2010)
This thesis spans two fields - South African dance and the philosophy of humour - and attempts to link them through an understanding of their formal mechanisms. I attempt to establish two main ideas: that there is a need for a critical praxis in South African dance, and that humour in dance can be part of this process. In Chapter One, I discuss elements of the South African dance and theatre industries pre- and post-1994 towards arguing my first point (that South African dance would benefit from a critical praxis). I probe some of the challenges facing artists and describe howchoreographers are dealing thematically and stylistically (but not formally) with the concept of the 'New' South Africa. Through an investigation of concerns voiced by critics regarding choreographic form in the country, I argue that South African dance would benefit from critical formal investigations in dance-making. Finally, I discuss traditional views of humour in South African dance/theatre and in philosophy, which suggest that humour is predominantly seen as frivolous and unworthy of serious attenfion. In Chapter Two, I offer a defence for humour's more profound critical aspects, suggesting that humour can in fact be seen as critical 'thinking in action'. A discussion of theories about humour reveals that the basis for humour is the incongruous. A subsequent discussion of form in theatre and dance shows how the incongruous might work within dance form to create meta-dance. In this way, I attempt to link the two fields of humour and South African dance and to make the connection between the critical capaci~ies of meta-dance and those of humour. I suggest, in other words, that humour in dance can create a critical awareness, of the likes advocated in Chapter One. In Chapter Three, I discuss aspects of two works: my own This part should be uncomfortable (2008) and Nelisiwe Xaba's Plasticization (2004). The two analyses differ from each other as does the humour in both works. Despite the differences, I argue that humour in both works is operating on a critical level that includes a meta-level of signification.
Keywords: Dance -- South Africa; Choreography -- South Africa; Dance criticism -- South Africa; Theater -- South Africa; South African wit and humor